Building the wireless Internet. - Elliott, C. (IEEE spectrum)
Everybody's talking about the wireless Internet, but what on earth is it? And who's building it? The trade press is adrift in a bewildering jumble of acronyms from the cellular telephony industry that claim to point the way. Or maybe dozens of LEOS (low-earth-orbiting satellites) will furnish the wireless Internet. Or perhaps it's really two way pagers on steroids-powered by WAP (the wireless access protocol). Proceeding from first principles, the author believes that none of the well-known technologies will, in the end, provide the wireless Internet. Instead a dark-horse technology-a ?pure Internet? system based on technology familiar from a multitude of wireless local-area networks (LANs)-has good grounds to prevail. The author discusses which RF frequency bands should be used for the Internet, the use of nanocells to build the network, and gives a brief outline of the economics involved